Development and validation of a novel clinical scoring system for short‐term prediction of death in dogs with acute pancreatitis. (15th February 2019) - Fabrès, Virginie; Dossin, Olivier; Reif, Clémence; Campos, Miguel; Freiche, Valerie; Maurey, Christelle; Pilot‐Storck, Fanny; Desquilbet, Loïc; Benchekroun, Ghita
Abstract : Background: Acute pancreatitis (AP) is associated with a high death rate in dogs, but accurate predictors of early death are still lacking. Objectives: To develop a scoring system for prediction of short‐term case fatality in dogs with AP. Animals: One hundred sixty‐nine dogs with AP including 138 dogs in the training cohort and 31 dogs in the validation cohort. Methods: Multicenter, retrospective cohort study. Survival analysis was used to assess the associations with short‐term death (within 30 days after admission). Independent predictors of death were identified by a stepwise selection method and used for the score calculation. Results: Death rate within 30 days after admission was 33% in the training cohort. Four independent risk factors for short‐term death were identified in the training cohort: presence of systemic inflammatory response syndrome, coagulation disorders, increased creatinine and ionized hypocalcemia. Canine Acute Pancreatitis Severity (CAPS) score was developed to predict short‐term death, integrating these 4 factors in a weighted way. A simplified version of CAPS score (sCAPS) including respiratory rate instead of SIRS was also assessed. The area under the receiver‐operating characteristic curve (AUC) of CAPS and sCAPS scores was 0.92 in the training cohort with an optimal cutoff of 11 (sensitivity, 89%; specificity, 90%) and 6 (sensitivity, 96%; specificity, 77%), respectively. CAPS and sCAPS score were validated in the validation cohort with respective AUC of 0.91 and 0.96. Conclusions and Clinical Importance: We propose 2 scoring systems that allow early and accurate prediction of short‐term death in dogs with AP.